Material Modeling Approach for Graphene Antenna Design - Rajni Bala; Anupma Marwaha; Sanjay Marwaha (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
For the last few decades, in the field of patch antenna design for wireless applications the researchers have gone through experimenting with almost all types of variations in shape and dimensions of patch element, substrate material, exploiting with patch and ground structure with slots. Very little attention has been given to explore the pioneering approach of using different patch material improving the performance of antennas in terahertz regime. The graphene material is lately being used as patch material as it possesses a number of desirable electromagnetic and mechanical properties that assists in providing flexible and reconfigurable antenna structure. The material tunable conductivity accounts for the superior electromagnetic properties. Hence the authors have presented the simplified analytical solution for graphene surface conductivity to be utilized to characterize the graphene antenna parameters.